Infância e errância: imagens da criança abandonada na ficção brasileira - Licia Soares de Souza (Estudos de Literatura Brasileira Contemporânea)
This text presents the semantic and mythic feature of childhood, indicating the ideas of innocence and purity that characterize the beginning of an existence. If these ideals configurate an edenic space that can determine the positiv e relationships that children establish with themselves and the adult world, in the nocturnal regime of imagination, the escape from this space indicates a negative deviation, capable of destroying a state of innocence. We observe this deviation in the del inquent children in Captains of the sand , by Jorge Amado, which, abandoned in the streets of Salvador, lose their world of purity looking for mechanisms of survival. Then, we investigate the children in City of God , by Paulo Lins, whose innocence is underm ined by the power of drug dealers such as Zé Miúdo/Pequeno. Finally, we conclude that Amado‟s work indicates the anomalies of a society of exclusion that allows children to be abandoned in the streets, as if he was predicting that this situation would get worse if the country did not apply policies of inclusion with revenue sharing, aiming at the quality of life of the population.